Analisis Pengaruh Profitabilitas, Leverage, Umur dan Ukuran Perusahaan, Komite Audit terhadap Manajemen Laba Pada Perusahaan Manufaktur yang Terdaftar Di BEI Periode 2017-2021 - Sarah, Ranti May; Hernawaty; Sari, Maya Macia (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to examine the effect of profitability, leverage, firm size, firm age and audit committee on earnings management. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period of 141 companies. By using a purposive sampling technique, a total sample of 65 companies was obtained. The analysis tool is multiple linear regression, where previously the classical assumption test was carried out. The results of the analysis of the effect of profitability, leverage, age and company size, audit committee on earnings management in manufacturing companies listed on the IDX for the 2017-2021 period, it can be concluded that the variables Profitability, Leverage, age and company size, audit committee have no influence on management earnings after being tested using the SPSS application version 25.